BENTUK, STRUKTUR DAN MAKNA RAGAM HIAS HOTEL SAHID KUSUMA - Eko Sri Haryanto (Institut Seni Indonesia Surakarta, 2016)
Dalem Kusumayudhan is a part of the Sahid Kusuma Hotel in Surakarta, and was formerly the residence of Kanjeng Gusti Pangeran Harya Kusumayudha, son of Paku  Buwana X.   It has changed ownership several times and been renovated on a number of occasions.  The last renovation being in the middle of 2008, as part of the owner’s strategy to attract more tourists to visit and stay in the Sahid Kusuma Hotel.